Foreign language virtual chat buddy - Yee, Daniel Sebastian (Nanyang Technological University, 2020)
This report describes in detail the 8-months journey comprising my Final Year Project (FYP). This project aims to take on the challenge that language learners face of not having a consistent avenue to verbally practise their newly acquired language skills, erecting a barrier from progressing it from its infancy to maturity. As such, the aim of the project is to build a solution that seeks to determine the relevant technological boundaries that limit how effective any potential solutions may be. Eventually, the form factor of a mobile application was chosen. Features such as speech-to-text, text-to-speech, translation, grammar correction, and a chatbot were implemented into the application, allowing users to engage in dynamic conversation with the French-speaking chatbot. In the end, most of the features were implemented rather successfully. However, due to resource constraints, it was unfeasible to implement a truly intelligent chat agent within the course of this FYP. However, the future is increasingly promising for the escalation of this project into a full-fledged venture, having received positive user validation in almost every of its aspects, while rapid technological breakthroughs in the area of Natural Language is quickly providing the missing piece to turn this foreign language virtual chat buddy into a truly groundbreaking product.